Sentimen Warganet Indonesia di Media Sosial terhadap Serial Bidaah dari Malaysia - Nurhidayah, Ika Amiliya; Ramadhani, Oktaviana; Mukoyimah (El Madani: Jurnal Dakwah dan Komunikasi Islam, 2025)
Bidaah, a Malaysian drama series that premiered on the Viu platform on March 6, 2025, has sparked public attention for its bold portrayal of religious deviation led by a charismatic figure. The show’s sensitive theme has generated diverse reactions from Indonesian audiences, making it a compelling subject for scholarly analysis. This study aims to examine Indonesian public sentiment toward the series on social media. Employing a descriptive qualitative approach, the research utilized Brand24, a digital monitoring tool, to collect data from various social media platforms. Public comments and opinions were analyzed to identify recurring patterns and sentiment tendencies. The findings indicate that positive sentiment (860 mentions) outweighed negative sentiment (587 mentions), suggesting that most Indonesian netizens responded to Bidaah’s depiction of religious deviation with openness rather than rejection. This study highlights the importance of digital public discourse analysis in understanding societal reactions to religious media content, and demonstrates the relevance of social monitoring technologies in contemporary communication research.